Towards greener cities: Evaluating urban green space accessibility using the 3-30-300 rule exampled on the city of Olomouc (Czech Republic) - Wagner Matěj; Květoňová Veronika; Jirmus René; Lehnert Michal (Moravian Geographical Reports, 2025)
The 3-30-300 rule outlines key principles for urban greenery, emphasising its role in promoting human health, well-being, and quality of life. It calls for equitable access to green spaces and an integrated approach to urban development. This study introduces a transferable methodology for applying the 3-30-300 rule, focusing on Czech cities. A notable feature of the study is its usage of a deep learning tool combined with freely available public data. The methodology was applied to all residential buildings in the city of Olomouc, providing specific results at both citywide and individual rule-component levels. The study also addresses the rule’s limitations, offering a realistic view of its practical application. This contributes to the broader discussion on the role of urban green spaces in creating more sustainable and liveable cities. The findings reveal that rule 3 is met for nearly all residential buildings in Olomouc. However, rule 30 appears unattainable in the city, with maximum neighbourhood canopy cover reaching only 22%. Only approximately 25% of residential buildings are situated within the recommended 300-metre radius of a park. Our research shows that the 3-30-300 rule is a feasible framework for measuring the availability of greenery in (Czech) cities; however, further methodological development is needed.